2005
DOI: 10.1142/s0219691305000907
|View full text |Cite
|
Sign up to set email alerts
|

A Discrete Queue, Fourier Sampling on Szegö Curves and Spitzer Formulas

Abstract: We consider a discrete-time multi-server queue for which the moments of the stationary queue length can be expressed in terms of series over the zeros in the closed unit disk of a queue-specific characteristic function. In many important cases these zeros can be considered to be located on a queue-specific curve, called generalized Szegö curve. By adopting a special parametrization of these Szegö curves, the relevant zeros occur as equidistant samples of a 2π-periodic function whose Fourier coefficients can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…In [22] the c l are shown to have exponential decay for β ≥ 1 (which covers in fact all practically relevant instances). It is further shown that for 0 ≤ β < 1 the c l have exponential decay if and only if…”
Section: Fourier Series Representationmentioning
confidence: 89%
See 4 more Smart Citations
“…In [22] the c l are shown to have exponential decay for β ≥ 1 (which covers in fact all practically relevant instances). It is further shown that for 0 ≤ β < 1 the c l have exponential decay if and only if…”
Section: Fourier Series Representationmentioning
confidence: 89%
“…The roots lie inside J, and satisfy (22). Since |A(z)| 1/s < |z| for all z ∈ J, it follows from Rouché's theorem that for each w k , the function z − w k A 1/s (z) has as many zeros inside J as z.…”
Section: Fourier Series Representationmentioning
confidence: 95%
See 3 more Smart Citations